Utilising radiographic incisor crown markers to determine incisor inclination on lateral headfilms - and experimental study on extracted teeth - Zietsman, S.T. (University of Pretoria, 2013)
Thesis (MChD (Orthodontics))--University of Pretoria, 2005.